ONE APP, TWO VERSIONS: TIKTOK AND THE PLATFORMIZATION FROM CHINA - Lin, Jian (AoIR Selected Papers of Internet Research, 2020)
By developing two versions of the same platform, TikTok manages to establish its business in two highly distinctive platform ecosystems. It represents the process of ‘platformization from China’ – the penetration of platform logics developed in the techno-political economy of China into the global society. Domestically the disruptive and infrastructural nature of the platform power is intermingled with and subject to Chinese state power, evidenced by the both restrictive (e.g. censorship) and promotional policies for internet economy. At the same time, the missing agenda to account for user privacy and civil rights in the online spaces also gives legislative immunity to Chinese platforms in advancing techniques of datafication and commodification. This uncanny system of governance fosters a highly innovative and commercialized platform ecology domestically to meet with regulatory requirements of the authorities, the financial interests of the capital and the monetary and expressive expectations of the users. However, these platform logics developed in the Chinese context seem to contradict the governing values of the international platform societies. Although internationally TikTok has adopted a more restrained approach in its affordances, commodification and content moderation, the platform remains susceptible for its potential supposed connection to the Chinese state and the concomitant censorship policy. If platforms developed in the American-centric ecosystem can easily identify themselves as global, then the challenge for Chinese platforms going global lies always on this figurative ‘Chineseness’, which is not necessarily defined by the content and culture, but by the techno-political logics embedded in the affordances and operational mechanisms.